Leaf tissue arrangement, preliminary phytochemical investigation and callus induction from the medicinal hemi-parasite Osyris alba L. - Mamoucha, S.; Christodoulakis, N.S. (International Journal of Pharmacognosy and Phytochemical Research, 2016)
Osyris alba is a dioecious shrub used in traditional medicine for its bioactive secondary metabolites. It is used for its antiparasitic, antimicrobial and anti-bleeding properties. In the present study the leaf tissue arrangement, histochemsitry and callus formation of Osyris alba L. were investigated. Leaves (fresh and fixed) were observed by light, polarized oight and electron microscopy. Fresh stem was also observed by light microscopy. The sub-cellular localization of secondary metabolites was detected. Furthermore, in vitro production of its secondary metabolite, by using cell cultures, was also preformed. The compact leaves are amphistomatic, with a single layer of epidermal cells and contain idioblasts cells with crystals. They react positively to histochemical reagents for the major groups of secondary metabolites. In the preliminary histochemical screening, in vitro cultured cells also gave positive results. In conclusion, the medicinal nature of the plant is attributed to its phytochemical profile. Plant cell culture technologies can be used for the production of its bioactive molecules. © 2016, International Journal of Pharmacognosy and Phytochemical Research. All rights reserved.
Keywords: Callus; Histochemistry; Leaf anatomy; medicinal plant; Mediterranean